Impact of Urban Urchins on the Nigerian Democratic Governance: A Study of Yan- Shara in Kaduna Metropolis 2015-2021 - Abubakar Bello, Balarabe (Kashere Journal of Politics and International Relations, 2023)
The thuggery has become a fractious phenomenon affecting individuals and democratic briskness in Kaduna State.The Yan Shara thugs move mostly in groups victimizing, terrorizing, intimidating, and injuring not only politicians but also innocent individuals at their homes, shops and on the streets which resulted in loss of lives and valuable properties in the State. It is against this background; therefore, this article attempts to examine the impact of Yan Shara thugs on democratic governance in spite of the measures adopted by governments to overcome the phenomenon in the state from 2015 to 2021. The objective of this article is to find out the factors responsible for the recurrence of Yan Shara thuggery on democratic governance and to assess the effectiveness of government policies and programmes designed to overcome the menace. Data was obtained through secondary sources. The study considered this assumption that, Yan Shara thuggery recurs frequently in Kaduna State because it is sponsored by the elites. Elite theory was adopted to serve as a theoretical base for this article. The findings of the study depicts that thuggery in the State is as a result of political manipulation, unemployment, illiteracy, poor governance, group sentiment, poverty, injustice and weak security agencies to mention but a few. Therefore, the study recommends among others that government should initiate programmes including awareness campaigns that will transform and dissuade the Yan Shara and intended thugs psychologically from involving into such violent behaviours within the State.